3D printing strategic deployment: the supply chain perspective. Issue 3 (6th February 2019) - Braziotis, Christos; Rogers, Helen; Jimo, Ajeseun
Abstract : Purpose: The emergence and application of 3D Printing (3DP) is changing the way products are developed and reach the customer, allowing for unprecedented customisation options. Past research has focussed on the modus operandi of the technology, providing indications for wider future adoption. 3DP is predicted to complement current production processes and is anticipated to have a profound effect on the value chain and, therefore, on supply chain (SC) management. Management-related 3DP research has, however, been largely fragmented in terms of analysing the strategic deployment of 3DP and the corresponding effects on performance objectives. The aim of this paper is to identify, define and exemplify typical 3DP deployment strategies pursued. Design/methodology/approach: The approach taken is a critical literature review, synthesising and interpreting past research on cross-industry deployment of 3DP, including illustrative examples. This enabled the development of a framework of current stage knowledge. Findings: Building on past research, the authors propose a conceptual framework to be used as a classification system for 3DP operations, based on process and SC level configurations across different industries. They discuss the potential impact on operations performance objectives and then highlight research gaps, proposing specific research avenues to enhance understanding of the effects of 3DP adoption on SCs. Practical implications: The proposed framework outlines strategic guidelines for 3DP and provides practitioners with the range of strategic options available for 3DP deployment and anticipated impacts on performance. Originality/value: The framework can be used to map 3DP deployment at an operational level and identify the likely impact on performance objectives. Relevant implications and a future research agenda are explored.